2021
DOI: 10.3390/nu13061973
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Oligosaccharide Profiles over 12 Months of Lactation: The Ulm SPATZ Health Study

Abstract: Human milk oligosaccharides (HMOs) have specific dose-dependent effects on child health outcomes. The HMO profile differs across mothers and is largely dependent on gene expression of specific transferase enzymes in the lactocytes. This study investigated the trajectories of absolute HMO concentrations at three time points during lactation, using a more accurate, robust, and extensively validated method for HMO quantification. We analyzed human milk sampled at 6 weeks (n = 682), 6 months (n = 448), and 12 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 54 publications
5
38
3
Order By: Relevance
“…In addition to maternal genetic predisposition linked to the expression pattern of Se and Le blood group genes, total amounts of HMOS also varied according to lactation stage. In line with others (e.g., [ 3 , 4 , 5 , 39 , 40 ]), we showed that the nTPA of selected HMOS dropped sharply to about half in the first 4 months and thereafter remained largely stable until the end of the first year postpartum. Our group recently showed similar results in a large number of samples ( n = 1203) from a birth cohort study conducted in South Germany [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition to maternal genetic predisposition linked to the expression pattern of Se and Le blood group genes, total amounts of HMOS also varied according to lactation stage. In line with others (e.g., [ 3 , 4 , 5 , 39 , 40 ]), we showed that the nTPA of selected HMOS dropped sharply to about half in the first 4 months and thereafter remained largely stable until the end of the first year postpartum. Our group recently showed similar results in a large number of samples ( n = 1203) from a birth cohort study conducted in South Germany [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…In line with others (e.g., [ 3 , 4 , 5 , 39 , 40 ]), we showed that the nTPA of selected HMOS dropped sharply to about half in the first 4 months and thereafter remained largely stable until the end of the first year postpartum. Our group recently showed similar results in a large number of samples ( n = 1203) from a birth cohort study conducted in South Germany [ 40 ]. In that study, we found that—in line with the decrease in total HMOS amounts—absolute concentrations of most individual HMOS decreased from 6 weeks to 6 months and 12 months postpartum.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…DSLNT is another major acidic HMO. In several previous studies, the level of DSLNT declined from colostrum to transitional milk to mature milk, but the longitudinal changes were not significant [ 37 , 38 ]. Conversely, unlike the findings reported, we found that the concentration of DSLNT in the 61–120 day stage rose dramatically to at least 1.5 times that at preceding stages.…”
Section: Discussionmentioning
confidence: 96%
“… 18 Hence, whether the HMO supplementation ultimately improves infant formula milk in a way that mimics the documented benefits of human milk remain to be further investigated. 42 , 44 …”
Section: Structure and Biological Roles Of Hmosmentioning
confidence: 99%